Increased Intracranial Pressure in the Setting of Enterovirus and Other Viral Meningitides. (12th April 2017) - Beal, Jules C.
Abstract : Increased intracranial pressure due to viral meningitis has not been widely discussed in the literature, although associations with Varicella and rarely Enterovirus have been described. Patients with increased intracranial pressure and cerebrospinal fluid analysis suggestive of a viral process are sometimes classified as having atypical idiopathic intracranial hypertension (IIH). However, a diagnosis of IIH requires normal cerebrospinal fluid, and therefore in these cases an infection with secondary intracranial hypertension may be a more likely diagnosis. Here seven patients are presented with elevated intracranial pressure and cerebrospinal fluid suggestive of viral or aseptic meningitis. Of these, 1 had Enterovirus and the remainder were diagnosed with nonspecific viral meningitis. These data suggest that viral meningitis may be associated with elevated intracranial pressure more often than is commonly recognized. Enterovirus has previously been associated with increased intracranial pressure only in rare case reports.